2022
DOI: 10.3390/molecules27123856
|View full text |Cite
|
Sign up to set email alerts
|

Imidazo[1,5-a]pyridine-Based Fluorescent Probes: A Photophysical Investigation in Liposome Models

Abstract: Imidazo[1,5-a]pyridine is a stable scaffold, widely used for the development of emissive compounds in many application fields (e.g., optoelectronics, coordination chemistry, sensors, chemical biology). Their compact shape along with remarkable photophysical properties make them suitable candidates as cell membrane probes. The study of the membrane dynamics, hydration, and fluidity is of importance to monitor the cellular health and to explore crucial biochemical pathways. In this context, five imidazo[1,5-a]py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…The emission centred at λ = 400-460 nm can be ascribed to an LC (ππ*) electronic transition, in agreement with the vibrational profile and with the assignment reported in the literature for Cu, Ir, and Re analogues [46][47][48][49]51]. In conclusion, negligible differences can be observed in the emission profiles in solution of mono-, bis-, and Imidazo [1,5-a]pyridine derivatives are well known in the literature as intense emitters [52][53][54][55][56]. Indeed, 3-phenyl-1-(pyridin-2-yl)imidazo[1,5-a]pyridine (L) displays an intense fluorescence emission centred at 463 nm (in dichloromethane solution), with a quantum yield of 19% and a remarkable Stokes shift of 79 nm [22,[57][58][59][60][61][62].…”
Section: Optical Characterizationsupporting
confidence: 90%
See 1 more Smart Citation
“…The emission centred at λ = 400-460 nm can be ascribed to an LC (ππ*) electronic transition, in agreement with the vibrational profile and with the assignment reported in the literature for Cu, Ir, and Re analogues [46][47][48][49]51]. In conclusion, negligible differences can be observed in the emission profiles in solution of mono-, bis-, and Imidazo [1,5-a]pyridine derivatives are well known in the literature as intense emitters [52][53][54][55][56]. Indeed, 3-phenyl-1-(pyridin-2-yl)imidazo[1,5-a]pyridine (L) displays an intense fluorescence emission centred at 463 nm (in dichloromethane solution), with a quantum yield of 19% and a remarkable Stokes shift of 79 nm [22,[57][58][59][60][61][62].…”
Section: Optical Characterizationsupporting
confidence: 90%
“…All the complexes show a small blue shift when compared to the corresponding free ligand and an intense increase in the low-energy band at about 380 nm. Imidazo [1,5-a]pyridine derivatives are well known in the literature as intense emitters [52][53][54][55][56]. Indeed, 3-phenyl-1-(pyridin-2-yl)imidazo[1,5-a]pyridine (L) displays an intense fluorescence emission centred at 463 nm (in dichloromethane solution), with a quantum yield of 19% and a remarkable Stokes shift of 79 nm [22,[57][58][59][60][61][62].…”
Section: Optical Characterizationmentioning
confidence: 99%
“…Currently, there are no commercial drugs containing this unit, but many studies have demonstrated the potential applicability of imidazo[1,5- a ]pyridines in pharmacology. In Figure 3 , diverse biologically active derivatives of imidazo[1,5- a ]pyridine are depicted, including agonists of cannabinoid receptor type 2 (CB2R) (compound 1 ), serotonin 5-hydroxytryptamine (5-HT4) antagonists (compound 2 ), inhibitors of hypoxia-inducible factor 1α (HIF-1α) (compound 3 ), inhibitors of indoleamine 2,3-dioxygenase (IDO) and tryptophan 2,3-dioxygenase (TDO) (compound 4 ), cribrostatin-6 (compound 5 ), phosphodiesterase 10A inhibitors (compound 6 ), tubulin polymerization inhibitors (compound 7 ), neurokinin antagonists, kinase inhibitors, and various chemotherapeutic agents that have been evaluated [ 65 , 75 , 76 , 87 , 92 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. In addition, in the past, this nucleus has been investigated as a selective, nonsteroidal inhibitor of aromatase for the treatment of estrogen-dependent disease [ 108 ].…”
Section: Studies and Applications Of Imidazopyridine Derivativesmentioning
confidence: 99%
“…The optoelectronic features of imidazo [1,5-a]pyridines and benzimidazoles are remarkable since the molecules based on them display unique photophysical properties with quantum yields ranging from moderate to high, huge Stokes shift, and good stability under the tested conditions. Specifically, applications of imidazo [1,5a]pyridines and benzimidazoles in organic optoelectronic materials include organic light-emitting devices (OLEDs) [30,31], nonlinear optic materials (NLOs) [32,33], photosensitizers based on organic metal complexes [34,35], fluorescence cell imaging [36,37], organic fluorescent probes [38][39][40][41][42], sensors and emitters for confocal microscopy [17] and so on. In the design of fluorescent dyes and fluorescent materials, introducing strong electron donors and extending the molecular π-conjugated system has been proven to be an efficient strategy to lengthen emission wavelengths as well as Stokes shifts [43][44][45][46][47][48] Besides, fluorescent dyes with electron donors can retain a relatively high fluorescent quantum yield, which is determined by the gap between frontier orbitals [49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%